Social interactions in New Zealand common bottlenose dolphins (Tursiops truncatus) : association dynamics, skin diseases and aggressive injuries, and variations in vocal signals : a thesis presented in partial fulfilment of the requirement for the degree of Doctor of Philosophy in Conservation Biology at Massey University, Auckland Campus, New Zealand - Patin̋o-Pérez, Jessica (Massey University, 2022)
Social behaviour is described as a series of interactions between two or more members of the same or different species that usually benefits all the individuals involved. Individuals form strong bonds because of these interactions, which might be cooperative, hostile, mutualistic, or altruistic. Depending on the nature of the relationships and participants, social behaviour can lead to the establishment of distinct social systems. Although it is evident that social behaviour does not have to be selfless, the question of why and how social behaviours occur in animals is still being debated. According to Krause and Ruxton (2002), sociality emerges when the advantages of long-term social contacts outweigh the drawbacks of such close relationships with conspecifics. Among the advantages of living in a group are increased opportunity for food and mating, as well as protection from predators. This sociality, on the other hand, might have negative implications, such as increased rivalry for mates and resources or increased disease transmission risks. I investigated multiple aspects of the social lives of common bottlenose dolphins Tursiops truncatus (hereafter bottlenose dolphins) in New Zealand. Historically, the north-eastern North Island bottlenose dolphin population has been intensively studied at the Bay of Islands since it was the only place where dolphins are constantly sighted. A rapid decline in this population and high calf mortality raised concern about the viability of this population. The key objective of my research was to understand how different social aspects influence the population of bottlenose dolphins at Great Barrier Island (GBI), New Zealand, an area that was recently describe as a ‘social hub’ for the species. Although, throughout my thesis I talk about the population of dolphins present in GBI, it is important to keep in mind that this is one part of the entire North Island population. In the first part of my thesis, I describe the social structure of bottlenose dolphins in GBI using historical data from the Bay of Islands (BOI) and GBI, in addition to my own data. I analysed their social structure by examining: (1) preferred/avoided companions, (2) strength and distribution of associations, (3) temporal and spatial patterning of associations, and (4) residence times. The analysis of BOI-GBI showed two distinct social communities, each of which is made up primarily of members photographed only in their respective areas. Only a few individuals were identified in both areas. For GBI, two datasets were analysed: 2011-2013 and 20015-2019. During both time periods, the population exhibited low levels of association, characteristic of fission-fusion societies like bottlenose dolphins, but the populations also showed some structure, with dolphins forming long-lasting bonds with some individual and avoiding others. Moreover, during 2015-2019, two social communities were identified in the population, exhibiting different ranging patterns and pattern of association within communities. The temporal analysis showed that during 2011-2013, the population exhibited a combination of stable associations among individuals and other individuals that associate, disassociate, and may reassociate again over extended periods of time. During 2015-2019, dolphins associate for short periods of times before breaking up, happening at two different times. Analysis of residency times during 2011-2013, showed that the models including emigration + reimmigration were the best to describe the population, while during 2015-2019, were the models including emigration/mortality. Bottlenose dolphins associate in groups that frequently change in size and composition, characteristic of fission-fusion societies. Skin lesions and tooth rakes can be used to assess natural and anthropogenic pressures within a population, which is useful information for better understanding population dynamics. In addition, tooth rake marks are a measure of the level of social contacts within a population and are usually the outcome of inter- and intra-specific interactions. Gregariousness is a major component in disease transmission and increases the likelihood of aggressive confrontations. When it comes to diseases, animals with a high incidence of interactions with others will increase the chances to spread diseases, putting their populations at risk. In this thesis, I described for the first time the prevalence of skin lesions and tooth rakes for the north-eastern population of bottlenose dolphins. In addition, I described the skin lesions found in, and determined the location of, the skin lesions and tooth rakes on dolphins’ bodies. I also proposed a protocol to assess skin lesions and what are the implications for future studies. Finally, I tested if there was an association between skin lesions and tooth rakes, and the strength of the dolphins in their social network. I wanted to know if presence or absence of tooth rakes was defined by the strength in their social network and if dolphins with a higher coverage score of tooth rakes will have a higher strength in their social network. In addition, I examined if tooth rake scores were different based on the presence and absence of skin lesions. From the literature, I found 19 skin lesions with distinct and non-overlapping definitions. These lesions were the foundation of the protocol that I used to assess lesion presence in my population. Eight skin lesions were present in bottlenose dolphins at Great Barrier Island, with different prevalence in the population and varying distribution across different parts of the dolphin body. Pale lesions had the highest prevalence at 84.4% and were found across four body parts, but mainly in the dorsal fin. Similarly, black lesions, white-fringe spots, nodules, and dark-fringe spot were found in four body parts but their prevalence in the population were lower (33.1%, 17.5%, 11.7%, and 15.6%, respectively). Finally, spotted lesions (10.4%), white fin fringe (5.84%), and tattoo-like disease (4.54%) had the lowest prevalence and were found in three, two, and one body region(s), respectively. Tooth rakes also had a high prevalence in the population (94%), and they were found mostly on the dorsal fin (100%, n = 150), followed by mid-flank (90.2%, n = 139), and anterior section (88.3%, n = 136). The mean coverage score did not change significantly over time (images were compared up to 20 months apart). From the 150 dolphins included in the tooth rake analysis, individuals sighted four or more times were included in the analysis of tooth rakes and strength of associations, giving a sample size of 50 dolphins. I found that the strength of the individual (i.e., it is the individual’s gregariousness) in the social network does not affect the tooth rakes an individual has and having tooth rakes is not dependent on strength. In addition, coverage score (a value obtained dividing the presence of skin lesions in 12 body parts by their visibility) did not change with the presence of skin lesions. In this chapter, I emphasised the need to determine the overall health of cetaceans in the North Island, as well as the need for more precise and systematic evaluations of the skin lesions of this population and other cetaceans in the region. Cetaceans are highly vocals animal that depend on sound to communicate, navigate, and find food. Most dolphins can produce three different types of sound, from which whistles have been the most studied due to this type of vocalisation being within the human hearing range and more easily visualised in spectrograms for analysis. Whistles are narrowband, frequency modulated sounds with strong harmonic structure and are used in social interactions. Geographic variation in whistle characteristics has been reported in many populations of bottlenose dolphins around the world and the causes of this variation are diverse. For the first time in New Zealand, I have compared the variation in whistle characteristics of two isolated populations of bottlenose dolphins, GBI and Fiordland, using seven time-frequency variables. In addition, I compared the parameters between these isolated populations using Random Forests analysis (RF) and assessed the influence of location, group size, and presence of immatures on these characteristics. Finally, I compared the whistle characteristics of bottlenose dolphin populations from around the world with New Zealand populations using a hierarchical cluster analysis. Whistle characteristics of both populations were similar to other populations around the world, surprisingly, my populations were similar to other populations from the northern rather than the southern hemisphere regions. A comparison of whistle parameters between GBI and Fiordland, showed that the Fiordland population had longer whistles and more inflection points than whistles from the GBI population. Whistles from these two populations were distinct enough to be correctly allocated to one population based on acoustic measures alone with a 90% of accuracy. The most important variables for classification were whistle type contour, duration, and end frequency. I obtained two principal components from the NIPALS PCA. The first principal component (PC1) explained 55.6% and the second component (PC2) explained 44.4% of the variance. Linear Mixed Models on PC1 and PC2 were used to assess whether whistles acoustic parameters were influenced by location, group size, and presence of immatures. I found that PC1 was not different between areas or with the presence of immatures. However, minimum frequency and duration differed between the two populations (location). Overall, my research has produced significant new knowledge on the social structure, prevalence of skin lesions and tooth rakes, and geographic variation in vocalisations of bottlenose dolphins. My research provides better understanding of the high degree of social and acoustic plasticity of bottlenose dolphins by applying state-of-the-art approaches such as social network and random forests analyses to multiple temporally and spatially diverse datasets. In addition, I developed a useful tool for non-invasive categorisation of infectious skin diseases that can be used by researchers and conservation practitioners worldwide to assess the health of individuals and populations.
Keywords: Bottlenose dolphin; Behavior; Diseases; Wounds and injuries; Vocalization; New Zealand; Great Barrier Island; 310901 Animal behaviour